Lifestyle Modifications and Oral Anti Diabetic Drugs in Treatment of Diabetes Mellitus - Yash Gupte; Sourya Acharya (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Insulin plays a crucial role in the body’s metabolic processes, especially glucose homeostasis. Hyperglycaemia can be caused by a relative or total absence of insulin, as observed in diabetes mellitus. Retinopathy, nephropathy, neuropathy, and cardiovascular problems may develop if not addressed. Control of blood sugar levels with insulin or glucose decreasing agents can delay or prevent progression to overt diabetes.